THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE - Laila, Amar’atus; Rohmawati, Ade Putri Indri; Hwihanus, Hwihanus (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of corporate social responsibility on the financial performance of a company. This research method uses a meta-analysis method with a data collection technique in the form of written documents and using books and journals. The data analysis that has been used is a qualitative descriptive approach. The findings of this study found that Corporate Social Responsibility (CSR) has an influence on the company's financial performance. Based on the results of existing studies show that there are differences of opinion regarding the positive and negative effects of CSR on financial performance. Some studies reveal a positive impact, while others reveal a negative or even insignificant impact. CSR disclosure can improve financial performance if it is done sincerely and provides information that meets stakeholder expectations. Well-managed CSR can benefit companies in the long run by involving all stakeholders in a fair and transparent manner